Communication and COVID-19 Physical Distancing Behavior Among Dutch Youth. Issue 1 (1st June 2021) - Rozendaal, Esther; van Woudenberg, Thabo; Crone, Eveline; Green, Kayla; van de Groep, Suzanne; de Leeuw, Rebecca; Sweijen, Sophie; Buijzen, Moniek
Background: Although most young people do not become seriously ill from the coronavirus causing the COVID-19 disease, they do play a role in its spread. It is therefore important that they adhere to the recommended preventive behaviors, most importantly, physical distancing. This study aims to gain a better understanding of the psychosocial determinants of young people's physical distancing behavior and the role that direct (i.e., interpersonal) and mediated communication (i.e., mass media, social media) about COVID-19 plays in this. Methods: A daily diary study was conducted among 481 Dutch adolescents (secondary school students; age range 10–18 years) and 404 young adults (university students; age range 17–25 years), involving 10 identical daily surveys administered on weekdays during a 2-week period during the first wave of the COVID-19 pandemic (May 2020). The hypotheses were tested with preregistered univariate and multivariate linear mixed-effects models. Results: The perceived descriptive norm (i.e., what friends are doing) was the most important determinant of physical distancing behavior among both adolescents and young adults. The perceived injunctive norm, perceived response efficacy, and perceived severity were also positively associated with physical distancing, albeit less strong. Among adolescents, exposure to information about COVID-19 in the mass media increased their perceptions of the descriptive norm, which in turn increased their physical distancing behavior. Conclusions: For those involved in studying and designing COVID-19-related behavioral interventions and campaigns targeting youth, it is important to consider the social norms that they relate to, and to take into account their perceived severity and response efficacy.